Comparison of transformation mechanisms of Haemophilus parainfluenzae and Haemophilus influenzae. - Barany, F (1985)
Transformation pathways in two closely related bacterial species, Haemophilus parainfluenzae and Haemophilus influenzae, were studied. Both organisms rapidly take up transforming DNA within minutes into specialized membranous structures on the cell surface (transformasomes). DNA within transformasomes is in a protected state, inaccessible to external DNase or internal restriction and modification enzymes. However, the subsequent processing of donor DNA differs in these two organisms. In H. influenzae, linear DNA immediately undergoes degradation from one end at a constant rate, leaving a lower-molecular-weight intermediate in the transformasome. The end undergoing degradation is searching for homologous regions of the chromosome. Once pairing is initiated, the remaining lower-molecular-weight DNA exits from the transformasome, and a single strand undergoes efficient integration. In contrast, in H. parainfluenzae little degradation of donor DNA is observed, with the majority remaining intact within the transformasomes after 1 h. Thus, whereas only 10% of donor DNA molecules leave the protected state after 1 h, portions of each molecule appear to become quantitatively integrated.